KOLABORASI MULTI STAKEHOLDER DALAM REVITALISASI KURIKULUM BERBASIS OUTCOME BASED EDUCATION PROGRAM STUDI MANAJEMEN PENDIDIKAN ISLAM - Jono Antoni; Idi Warsah; Adisel; Jumira Warlijasusi (TADBIRUNA: Jurnal Manajemen Pendidikan Islam, 2025)
In the era of Industry 4.0 transitioning to Society 5.0, higher education institutions are required to transform through Outcome-Based Education (OBE) curricula that support Merdeka Belajar Kampus Merdeka (MBKM). This article aims to analyze the importance of multi stakeholder collaboration in revitalizing the OBE curriculum in the Islamic Education Management Study Program to produce excellent human resources. The study employs a literature review approach using Mendelow's Stakeholder Matrix, categorizing stakeholders into four quadrants: Latents, Promoters, Apathetics, and Defenders. The findings reveal that active stakeholder engagement, especially transitioning their roles towards the Promoters quadrant, is crucial for curriculum revitalization success. The Head of the Study Program plays a pivotal role in managing communication strategies to ensure sustainable collaboration. In conclusion, effective multi stakeholder collaboration enhances the quality of higher education in Islamic Education Management Study Programs and supports the achievement of Indonesia’s Golden Vision 2045